Diversification Strategies in Developing SMEs Engaging with Local Dairy Milk Products - Setiaji, K; Firdam Setiadi, Y (KnE Social Sciences, 2018)
Salatiga is one largest dairy milk producer in Central Java. Stasiun Susu is the first SME engaging with diary milk production in Salatiga and greatly influences the diary milk product innovations. In developing its businesses, Stasiun Susu implements five diversification dimensions, including product, service, personal, channel, and image. This qualitative research employs a case study approach to examine and figure out models of diversification strategies used by SME Stasiun Susu in Salatiga. The research results show that the diversification strategies have made various contributions to the development of Stasiun Susu , such as (a) the dairy products have more than 70 flavor variants and highly emphasize on milk quality; (b) implementing the concept of homey-based services; (c) having strong and competent leaders in various fields, (d) no branches as one Stasiun Susu strategy; and (e) having a strong image in line with its philosophy ”when people are looking for milk, Stasiun Susu is the place”. Stasiun Susu should have further diversified its milk into food products, such as yoghurt, milk tofu, chips, or dodol. Keywords: business strategy, diversification, SME development